Poverty Alleviation Strategy in Jeneponto Regency - zainal, henni (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Poverty is a complex social problem that is still a challenge in many regions in Indonesia, including Jeneponto Regency. This research aims to investigate the poverty alleviation strategies that have been implemented in Jeneponto and analyze the factors that influence the success or failure of these strategies. Through a qualitative approach, data was collected through interviews with relevant stakeholders, field observations, and analysis of documents related to poverty alleviation policies and programs. The research results show that the poverty alleviation strategy in Jeneponto includes various programs and policies, such as community economic empowerment, increasing access to education and health, and basic infrastructure. Factors that influence the success of this strategy include inter-agency coordination, community participation, and adequate resource allocation. However, challenges such as budget limitations, unequal distribution of program benefits, and changes in economic and environmental conditions remain obstacles that need to be overcome. In this context, this research produces recommendations for increasing the effectiveness of poverty alleviation strategies in Jeneponto, including increasing inter-agency coordination, strengthening community participation, and adapting policies to existing local dynamics. Thus, it is hoped that this research can contribute to more effective and sustainable poverty alleviation efforts in Jeneponto Regency.